2022
DOI: 10.3389/fvets.2022.859041
|View full text |Cite
|
Sign up to set email alerts
|

Aging in Cats: Owner Observations and Clinical Finding in 206 Mature Cats at Enrolment to the Cat Prospective Aging and Welfare Study

Abstract: Two hundred and six cats, aged between 7 and 10 years, from the North-west of the UK, were enrolled in a cat aging and welfare study to determine the frequency of age-related conditions and associations with husbandry, owner observations of physical appearance, activity and behavior. This is the largest study to date of mature cats that includes data from an owner questionnaire and clinical examinations. At enrolment, owners frequently reported physical changes (53%), behavioral changes (47%), changes to eatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 70 publications
(93 reference statements)
0
9
0
Order By: Relevance
“…Where possible, the heart should be auscultated on a number of occasions during the examination as the heart rate and detectability of a heart murmur will vary throughout the examination. 98 For evaluation of musculoskeletal disease (predominantly dJd), a combination of physical examination and caregiver assessment is essential, as caregivers may have recognized changes in their cat's normal behaviors and mobility. 99,100 Several questionnaires have been validated for this purpose, and can be provided to caregivers in advance of the appointment.…”
Section: How To Perform a Cat Friendly Physical Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Where possible, the heart should be auscultated on a number of occasions during the examination as the heart rate and detectability of a heart murmur will vary throughout the examination. 98 For evaluation of musculoskeletal disease (predominantly dJd), a combination of physical examination and caregiver assessment is essential, as caregivers may have recognized changes in their cat's normal behaviors and mobility. 99,100 Several questionnaires have been validated for this purpose, and can be provided to caregivers in advance of the appointment.…”
Section: How To Perform a Cat Friendly Physical Examinationmentioning
confidence: 99%
“…Where possible, the heart should be auscultated on a number of occasions during the examination as the heart rate and detectability of a heart murmur will vary throughout the examination. 98…”
Section: How To Perform a Cat Friendly Physical Examinationmentioning
confidence: 99%
“…In a study in the United States, approximately 20% of pet cats were eleven years of age or older [ 166 ]; and a 2017 study in the UK showed a median age of 6.2 years in cats presenting to veterinary clinics, with cats aged more than eight years representing more than 40% of feline consultations [ 167 ]. Ageing is a continuous and slow process that compromises the normal functioning of various organs and systems in both qualitative and quantitative terms [ 168 ], and has been defined as a complex process in which the individual suffers from a decline in physical condition, organ, sensory and mental function, as well as immune response [ 169 , 170 ]. Obviously, there is a great individual variation between biological and chronological age and how the body systems age in each individual, meaning that geriatric abnormalities or diseases can appear earlier in some cats and never appear in others.…”
Section: Geriatric Catsmentioning
confidence: 99%
“…However, chasing and stalking are also indicative of play behavior in cats, and thus may not be negative for all cats involved. As cats age, they are at an increased risk of developing diseases which may cause pain or discomfort ( 39 ), and thus their tolerance of interactions with other cats may change. The age at which cats are weaned from their mother also impacts the inter-cat relationship, with early weaned cats (< 8 weeks of age) more likely to show aggression toward other cats ( 40 ).…”
Section: Introductionmentioning
confidence: 99%